Efektivitas Kepengurusan Status Perkawinan Belum Tercatat Melalui Program Jemput Bola Di Kelurahan Kalirungkut - Mutiara Cahyani; Radjikan Radjikan (Jurnal Relasi Publik, 2024)
Research on the effectiveness of unrecorded marriage status services through jemput bola program in the Kelurahan Kalirungkut uses the effectiveness theory of Sutrisno which has five variables, namely program related understanding, right on target, on time, achievement of goals, and real change. The research was carried out in Kelurahan Kalirungkut, Surabaya City, Province East Java. The aim of the study was to find out the effectiveness of jemput bola program for unrecorded marriage status services carried out by interns for the data target. The research method uses a qualitative approach to the type of descriptive research. Data is collected from observations, interviews, and literary studies of previous research. The results of the research show that the implementation jemput bola program has been effective except in terms of on time because there still a lot of target data with their unrecorded marriage status due to limited executor in the field.